LAW ENFORCEMENT AGAINST TRADEMARK INFRINGEMENT IN INDONESIA: Received: 04th April 2024 Revised: 24th May 2024, 28th May 2024, 31st May 2024 Accepted: 09th April 2024 - Etty Indrawati (MATTER: International Journal of Science and Technology, 2024)
Trademark as part of intellectual property rights is one of the most important elements in the business world. The number of trademark infringements that occurred in Indonesia from 2015 to 2023 shows an increasing trend. The purposes of this research are to explore and analyze the cause of trademark infringement and to investigate how efforts should be made to solve and reduce the number of trademark infringements in Indonesia. This research is normative legal research underpinned by interviews as well as through library research. Interviews were conducted with resource persons using interview guidelines. Then, data were analyzed using qualitative analysis. The result shows that the reason for trademark infringement is economic reasons. The offending party has bad intentions and assumes that the business whose trademark is to be imitated has good potential and person concerned can obtain a reasonable profit (good turnover potential) if using the same or similar trademark. The second is the party whose trademark is used by another party without rights needs to make a complaint about the trademark infringement because the infringement of intellectual property rights (including trademark infringement) is a complaint of violation that must be reported by the injured party to the law enforcer.